Respon Siswa Terhadap Pengenalan Literasi Matematika Melalui Permainan Kartu - Anis Munfarikhatin; Markus Palobo; Dian Mayasari (Musamus Journal of Mathematics Education, 2020)
The purpose of this study is to determine student responses after being given an introduction to mathematical literacy using card media. Literacy cards contain literacy contexts in everyday life that are associated with commonly encountered problems. The research method used is descriptive qualitative using instruments in the form of questionnaire student responses. The questionnaire was prepared and tested for validity by expert validators. There were three dimensions developed in this questionnaire including the appearance of card media, the usefulness of literacy cards, and the suitability of using literacy cards. Each dimension was then developed into an indicator and elaborated on several questionnaire points. The subjects of this study were eighth grade students, totaling 18 students. The results were analyzed using microsoft excel to determine the level of student response. A description of the results was carried out to provide a clear picture of each indicator. Based on the results, it obtained on the display indicators and content of literacy cards as much as 68% agree, ease of use of literacy cards as much as 70% and the usefulness of literacy cards by 71% which shows that the interpretation of literacy recognition through card games gives a good response by respondents.